2020
DOI: 10.3389/fvets.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Toward Antibiotic Stewardship: Route of Antibiotic Administration Impacts the Microbiota and Resistance Gene Diversity in Swine Feces

Abstract: Sequencing of plasmid-enriched samples revealed multiple genetic contexts for the resistance genes detected and highlighted the potential role of small plasmids in the movement of antibiotic resistance genes. The findings are informative for disease management in food animals, but also manure management and antibiotic therapy in human medicine for improved antibiotic stewardship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 73 publications
2
46
0
Order By: Relevance
“…Tetracyclines and sulfonamides are two classes of antibiotics often used in veterinary medicine due to their broad-spectrum activity, relatively low toxicity and low price [53,54]. After administration, most tetracyclines are excreted as active compounds through feces and urine, which are spread in the environment by manure fertilization practices [55,56]. These compounds have a high affinity for soil organic matter [57].…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
“…Tetracyclines and sulfonamides are two classes of antibiotics often used in veterinary medicine due to their broad-spectrum activity, relatively low toxicity and low price [53,54]. After administration, most tetracyclines are excreted as active compounds through feces and urine, which are spread in the environment by manure fertilization practices [55,56]. These compounds have a high affinity for soil organic matter [57].…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
“…The quantity of these components is higher when the pigs are treated with antibiotics than when the pigs are not treated. As stated in Section 2.1, this increase is greater when the antibiotics are administered in feed than when they are administered by injection [25].…”
Section: From Pig To Environmentmentioning
confidence: 92%
“…Holmer et al have argued that the increase in strains of E. coli resistant to florfenicol may be due to co-selection with another given antibiotic or when pigs are treated for respiratory infections. Another study demonstrated that using tetracycline in pigs prompted co-selection for resistance genes for aminoglycosides and tetracycline [25]. These studies illustrate the importance of taking a wider view of antibiotic resistance.…”
Section: Therapeutic Use Of Antibioticsmentioning
confidence: 96%
See 2 more Smart Citations